Is hyperammonemia helpful in detecting syndromic tubulopathies with early extrarenal manifestations? A case report of Lowe's syndrome - Agnieszka Jędzura; Monika Dębowska; Piotr Adamczyk (SpringerOpen, 2024)
Abstract Background Generally, it is not well known that Lowe's syndrome may coexist with hyperammonemia and hipocarnitynemia. The importance of hyperammonemia in the diagnosis of kidney diseases is not completely understood. Case presentation We present the history of a 13-year-old boy, admitted to the hospital due to proteinuria. In the past, the boy was diagnosed with binocular cataracts in infancy. Then he went through neurological diagnostic tests which diagnosed muscular hypotonia and psychomotor retardation but no inherited errors of metabolism were found. Proteinuria has been observed since the age of 2. Ultrasound imaging at the age of 5 showed the presence of a shading deposit in the kidney. At the age of 13, the boy was referred to the Pediatric Nephrology Ward. The laboratory tests revealed: a reduction of glomerular filtration rate, metabolic acidosis, proteinuria, hypercalciuria, increased activity of AST (SGOT), CK, LDH, hyperammonemia, and decreased concentration of total carnitine in blood serum. Based on the clinical presentation, Lowe's syndrome was diagnosed. The genetic testing revealed an OCRL gene hemizygous mutation. Conclusion Lowe's syndrome is an example of a disease in which clinical symptoms-although occurring early and in high intensity-may not raise the suspicion of tubulopathy for a long time if they are not analyzed in a complex manner. There is a necessity to educate healthcare practitioners from other fields about the extrarenal symptoms of genetically determined tubulopathies. l-carnitine deficiency may be a symptom of proximal tubulopathy, including Lowe's syndrome. l-carnitine deficiency leads to disturbances in the efficiency of the urea cycle, which results in hyperammonemia. Hyperammonemia is not only a symptom of inborn errors of metabolism and liver failure, but it may also lead to the diagnosis of tubulopathy. Since carnitine supplementation could have the desired beneficial effect on the patient's general condition, it is postulated to conduct further studies on larger groups of patients with Lowe's syndrome.